2020
DOI: 10.3389/fpubh.2020.00260
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility, Acceptability, and Influence of mHealth-Supported N-of-1 Trials for Enhanced Cognitive and Emotional Well-Being in US Volunteers

Abstract: Kravitz et al. N-of-1 Trials for Emotional Well-Being We conclude that N-of-1 behavioral trials can be appealing to a broad albeit highly educated and mostly female audience, that usability was acceptable, and that N-of-1 behavioral trials may have the greatest utility among those most skeptical of the intervention to begin with.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Karkar et al have demonstrated how smart technology might be used by patients to experiment and test individual dietary triggers for irritable bowel disease [ 27 ]. Kravitz et al demonstrated it is possible to recruit a large (if somewhat biased) population (n = 447) to conduct their own cross-over N-of-1 trials to test treatments to enhance cognitive and emotional wellbeing [ 42 ]. Interestingly, those participants with the lowest expectations of the treatment experienced the greatest gains [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Karkar et al have demonstrated how smart technology might be used by patients to experiment and test individual dietary triggers for irritable bowel disease [ 27 ]. Kravitz et al demonstrated it is possible to recruit a large (if somewhat biased) population (n = 447) to conduct their own cross-over N-of-1 trials to test treatments to enhance cognitive and emotional wellbeing [ 42 ]. Interestingly, those participants with the lowest expectations of the treatment experienced the greatest gains [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another way to reduce costs and barriers is to make it easier for individuals to find relevant trials (or to design their own), complete enrollment procedures, and provide meaningful informed consent. A number of electronic platforms, many created for use on mobile devices, have been used or are in development (Barr et al, 2015;Konigorski et al, 2020;(Kravitz et al, 2020). As point out, however, For clinicians interested in embedding N-of-1 trials in their clinical practice, a personalized trial platform needs to be developed that allows users to customize trial designs according to the use case.…”
Section: Reducing Costs and Burdensmentioning
confidence: 99%
“…Successful implementations of N-of-1 trials using mobile applications are becoming more common Kaplan et al, 2022;Kravitz et al, 2018Kravitz et al, , 2020Marcus et al, 2022). The display in Figure 3 was generated on a mobile phone using an application developed specially for the I-STOP-AFib study.…”
Section: Practical Issuesmentioning
confidence: 99%